Perception of competence, mood state and stress tolerance in young high performance athletes - Arruza, José Antonio; Arribas, Silvia; Otaegi, Oihane; González, Oscar; Irazusta, Susana; Ruiz, Luis Miguel (Anales de Psicología / Annals of Psychology, 2011)
This study analyzed the role that perceived competence played in the mood state and the stress tolerance of young athletes. Thirty young athletes belonging to 10 different types of sports participated in this study. The results evidenced that high perceived competence had high negative correlations related to the dimension of stress generators, and positive correlations with the dimensions of stress recovery. Furthermore, perceived competence showed negative correlation with fatigue. These data indicates that perceived competence works as a nuclear element and mediator of psychological variables that play an important role in the performance of young athletes.